Establishment and characterization of Newcastle disease virus (NDV) persistently-infected colorectal cancer cell lines - Chan, Lee Chin (2022)
Newcastle disease virus (NDV) is an avian paramyxovirus that causes Newcastle disease (ND) outbreak worldwide. For the last few decades, NDV has been studied extensively for its oncolytic effect in various cancer cell lines both in vitro and in vivo. For some strains, they have entered several phases of clinical trials. Recently, studies showed that NDV persistent infection in cancer cell lines emerged which resulted in a development of populations of cancer cells that resisted the oncolytic effect of the virus. Nevertheless, the impact of the persistent infection on the cancer cells, phenotypically and genotypically, is yet to be elucidate. Therefore, the aim of this study was to investigate the phenotypic and genotypic of the NDV persistently-infected colorectal cancer (CRC) cell. To achieve this objective, three CRC cell lines, namely, LoVo, RKO, and HCT116p53+/+ were challenged with recombinant NDV expressing green fluorescent protein (rAF-GFP). Following prolonged infection, NDV-resistant subpopulation in each cell line emerged. These cell lines were designated as LoVoPI, RKOPI and HCT116p53+/+PI, respectively. Flow cytometry analysis showed that all these PI cells expressed GFP signal, despite diverse in expression level, confirming the presence of actively replicating NDV within the cells. During NDV reinfection, these PI cells resisted NDV-mediated oncolysis, continued to grow, and produce infectious plaques-forming virus progenies. The phenotypic characteristics of these PI cells such as invasiveness and tumourigenicity were investigated via cell migration assay, colony formation assay, and spheroid formation assay. Results revealed that all PI cells have significantly reduced migration ability and formed lesser colonies compared to that of their parental counterpart. In spheroid formation assay, LoVoPI and HCT116p53+/+PI formed smaller size of spheroid compared to their parental cells while RKOPI did not integrate into an intact spheroid, suggesting that persistent infection of NDV negatively affect the tumourigenicity of the PI cells. Despite their resistant towards NDV infection, a subpopulation in all the mock-infected PI cells were stained positive for Annexin V or 7-AAD, suggesting these PI cells exhibited an elevated basal level of apoptotic cell populations. We further challenged the PI cells with apoptosis-inducer 5-fluororacil (5-FU) and the results showed that all the PI cells were significantly more sensitive to 5-FU treatment compared to their parental cells. One of the mechanism of NDV mediated oncolysis is via caspase-dependent apoptotic pathway. None of the caspases were upregulated in PI cells suggesting that other apoptotic mechanisms might be involved. Therefore, we examined the expression of Bcl-2 family proteins including pro-survival Bcl-2 proteins (Bcl-2, Mcl-1 & Bcl-xL), pro-apoptotic Bcl-2 proteins (Bax, Bak & Bim) and inhibitor of apoptosis (IAP) protein (Survivin) in these PI cells. Western blot results revealed the elevated expression of the pro-survival Bcl-2 proteins and Survivin proteins in LoVoPI and RKOPI cells, suggesting that these proteins were critical in promoting the survival of PI cells. Knockdown of Survivin by small interfering RNA (siRNA) enhanced the NDV-mediated apoptosis in RKOPI and HCT116p53+/+PI but not in LoVoPI; knockdown of Bcl-2 however did not enhance the NDV-mediated apoptosis in all PI cells. Overall, our study revealed that NDV persistent infection may confer clinical benefits as the PI cells were attenuated in their tumourigenicity and became more sensitive to apoptotic inducer.